2022
DOI: 10.3389/fpls.2022.858519
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evaluation of Inflorescences’ Morphological Attributes for Yield Optimization of Medicinal Cannabis Cultivars

Abstract: In recent decades with the reacknowledgment of the medicinal properties of Cannabis sativa L. (cannabis) plants, there is an increased demand for high performing cultivars that can deliver quality products for various applications. However, scientific knowledge that can facilitate the generation of advanced cannabis cultivars is scarce. In order to improve cannabis breeding and optimize cultivation techniques, the current study aimed to examine the morphological attributes of cannabis inflorescences using nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…These observations support Woods et al (2021) [ 77 ], suggesting that the loci of agronomic and biochemical traits are predominantly independent of each other. Regarding morphological parameters and cannabinoid productivity, our previous prediction equation for IDB showed the efficacy of Inf.W measurements in forecasting inflorescences yield [ 59 ], and building on this data, the current findings uncovered a positive relationship also between Inf.W and TCPP ( Figure 3 ). Moreover, the positive association between TCPP and PH indicates that regardless of the genotypic partitioning based on the main cannabinoid profiles, high-stature plants are more productive ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…These observations support Woods et al (2021) [ 77 ], suggesting that the loci of agronomic and biochemical traits are predominantly independent of each other. Regarding morphological parameters and cannabinoid productivity, our previous prediction equation for IDB showed the efficacy of Inf.W measurements in forecasting inflorescences yield [ 59 ], and building on this data, the current findings uncovered a positive relationship also between Inf.W and TCPP ( Figure 3 ). Moreover, the positive association between TCPP and PH indicates that regardless of the genotypic partitioning based on the main cannabinoid profiles, high-stature plants are more productive ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 63%
“…Previously, broad inconsistencies were identified across the physiological and phenological traits of the intact plant [ 60 ] as well as across the inflorescence morphological attributes [ 59 ] among genotypes that are vernacularly associated with the same strain groups. The current study extends these findings and demonstrates that this inconsistency applies also to the plant’s cannabinoid profile ( Figure 2 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coffman and Gentner (1975) [49] observed that, as plant height increased, the concentration of THC in the leaf tissue generally decreased. However, other floral characteristics besides the inflorescence biomass (such as the number of flowers, length, width, uniformity, perimeter, and distribution) should be explored, as they can influence the final productivity [50].…”
Section: Phytocannabinoids Production and Management Techniques In Ca...mentioning
confidence: 99%